A System for Controlling Surface Temperature (International Journal of Innovative Research in Engineering & Management, 2021)
Temperature measurement using appropriate sensors and controls  is critical not only for environmental and weather monitoring, but  also for a variety of industrial processes. Temperature control  refers to activities that aim to keep a certain region's temperature  within a defined range or at a certain maximum/minimum level.  Many temperature control systems have been created, however  they all have certain drawbacks or flaws in terms of cost,  accuracy, and control area. Researchers suggested this Surface  temperature control technology to address these issues. The  thermostat, peltier element, display screen, control unit,  emergency button, and transducer with capacitor are all part of  this system. This system is less expensive and has higher  precision than other existing systems since it uses a transducer to  provide electricity and only operates when the temperature is less  or more than the specified value. These systems can be further  customised by including new technologies that are now  unavailable but will become popular in the coming years. As a  result, the future of Surface temperature control systems seems  promising.
Keywords: Control System; Peltier; Temperature; Thermostat; Transducer